2014
DOI: 10.1039/c3ra47734g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ion doping on the electrochemical performances of LiFePO4–Li3V2(PO4)3composite cathode materials

Abstract: This review highlights the effect of ion doping on the electrochemical performances of LiFePO4–Li3V2(PO4)3 composite cathode materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 77 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…[263][264][265][266] The choice of cathode material plays an essential role in the life cycle, cost, and energy density in lithium-ion batteries. 262,267,268 Chapter 5. Quantum-chemical approach to NMR chemical shifts in paramagnetic solids of their thermal stability, high energy density, high theoretical specific capacities, low cost, and environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%
“…[263][264][265][266] The choice of cathode material plays an essential role in the life cycle, cost, and energy density in lithium-ion batteries. 262,267,268 Chapter 5. Quantum-chemical approach to NMR chemical shifts in paramagnetic solids of their thermal stability, high energy density, high theoretical specific capacities, low cost, and environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium Iron Phosphate (LiFePO 4 [70]. Among them, Jin et al group had concluded that coatings based on LFP-LVP composite materials had shown better electrochemical properties with an excellent capacity retention rate of 73.3 % and increased cycling stability [70]. It is because these composite materials have large number of defects which would greatly increase the electrochemical property of the battery.…”
Section: Coatings For Batteriesmentioning
confidence: 98%
“…Apart from anode, the cathode part is also considered to be significant for attaining batteries with high energy density, high rate capability, and long cycle life. Lithium Iron Phosphate (LiFePO 4 [70]. Among them, Jin et al group had concluded that coatings based on LFP-LVP composite materials had shown better electrochemical properties with an excellent capacity retention rate of 73.3 % and increased cycling stability [70].…”
Section: Coatings For Batteriesmentioning
confidence: 98%
“…Lithium iron phosphate (LiFePO 4 ) as a very promising active material attracts much attention for electrical vehicles because of its low toxicity, high safety, potentially low cost, excellent life cycle, high structural stability, and large theoretical capacity (170 mA h g À1 ), among others [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. However, the kinetic performance of LiFePO 4 suffers significantly from poor electronic conductivity and slow lithium-ion transport.…”
Section: Introductionmentioning
confidence: 99%
“…However, the kinetic performance of LiFePO 4 suffers significantly from poor electronic conductivity and slow lithium-ion transport. To overcome the disadvantages, the performance was improved by decreasing the particle size, performing a surface modification, doping with other elements, coating with conductive material, and so on [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Nevertheless, to be useful for electric vehicles or high power energy storage, the active material of a Li-ion battery should be coated with a foil type current collector that is much thinner, and its electrode area should be large enough to meet the high power performance with a sufficient capacity.…”
Section: Introductionmentioning
confidence: 99%